Sologubs Schopenhauerrezeption und ihre Bedeutung fuer die Motivgestaltung in seinen Erzaehlungen - Šemjatova, Bärbel (Slavistische Beitraege, 1997)
The present work deals with the question to what extent in Sologub's narratives his Schopenhauer reception is expressed, especially in the selection and design of figure types and symbols, which are used by him in these narratives again and again.